Решите уравнение используя введение новой переменной: (х2+2х) 2-2×(х2+2х)-3=0

Aksiomsa868589 Aksiomsa868589    1   22.08.2019 18:50    3

Ответы
lixonilya lixonilya  05.10.2020 13:11
Пусть x^2 + 2x = t, тогда
t^2 - 2t  - 3=  0
D = 4 + 12 = 16 = 4^2
t1 = (2  +4)/2 = 6/2 = 3
t2  =( 2 - 4)/2 = - 2/2 = - 1

Два случая
1) x^2 + 2x = 3
x^2 + 2x - 3 = 0 
D = 4 + 12= 16 = 4^2
x1 = ( - 2 + 4)/2 = 2/2 = 1
x2  = ( - 2 - 4)/2 = - 6/2 = - 3

2) x^2 + 2x = - 1
x^2 + 2x + 1 = 0 
(x + 1)^2 = 0 
x + 1 = 0 
x3 = - 1

ответ
- 3; - 1; 1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра